Analisis Pertimbangan Hukum Hakim dalam Putusan Pailit Terkait Eksistensi Putusan Pengadilan Hubungan Industrial dalam Permohonan Pailit : Studi Putusan-Putusan Pailit - Wilson Lidjon; Sunarmi; Suhaidi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Analysis Of Judicial ' legal reasoning occurs between the Semarang Commercial Court Decision Number 5/Pdt.Sus-Pailit/2022/PN.Smg, which granted the bankruptcy petition against PT SM and the Supreme Court Decision Number 993K/Pdt.Sus-Pailit/2022, which annulled it on the grounds that no legally binding Industrial Relations Court (IRC) judgment had yet been issued. Using a normative-qualitative method, this study finds that the cassation decision creates legal uncertainty, as the Joint Agreement Number 01/PB-PT.SM/HRDGA/I/2022 had in fact satisfied the requirements for simple proof of debt under Article 2 paragraph (1) in conjunction with Article 8 paragraph (4) of the Bankruptcy Law, yet was deemed insufficient without the IRC prerequisite stipulated in SEMA 2/2019. This study recommends an amendment to the Bankruptcy Law that explicitly regulates bankruptcy proceedings against companies that fail to fulfill workers' rights.